(untitled) (Qualitative Research Journal for Social Studies, 2026)
Emojis are often seen as tools that make communication easier; however, the conditions where they cause misunderstanding are not fully clear, especially in non-Western digital settings. This study looks at emoji-related pragmatic failure in Pakistani online communication, focusing on Instagram as a space where images and text work together. A sociopragmatic approach is used. Fifty Pakistani participants from different age groups took part. They interpreted real Instagram posts where emojis were used in captions and conversations. The results show that misunderstanding is strongly linked to age differences. Younger users often give emojis ironic or shifted meanings based on online culture. Older users tend to interpret the same emoji in a direct and literal way. This creates clear gaps in understanding. Platform use also matters. Cultural meanings attached to emojis add another layer of confusion. These patterns suggest that emoji misunderstanding is not random. It follows social and pragmatic rules shaped by age, digital experience, and cultural knowledge. Therefore, the study provides one of the first focused examinations of emoji-related pragmatic failure in Pakistani digital communication. It also highlights the need for further research in digital sociopragmatics in non-Western contexts.